IN UZBEKISTAN BY CHROMATO-MASS SPECTROSCOPIC METHOD ANALYSIS OF MEDICINAL PLANTS (HYBRID METHOD OF ANALYSIS) - Haydarov G‘ayrat Shoyimovich; Satimov Farrux Zafarovich (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
When analyzing medicinal substances by chromatography-mass spectroscopic method, this is a method of checking their mass according to the spectrum of atoms and molecules in the substance. Analysis of inorganic compounds and elements in medicinal plants by chromatography-mass spectroscopic method often helps determine isotopes in substances and is aimed at their identification and determination of the structure. Therefore, the chromatographic separation of esters from the caraway plant, which belongs to the caraway family, is an urgent task today.